Love Food: Exchange and Sustenance in the Cook Islands Diaspora - Alexeyeff, Kalissa (The Australian journal of anthropology, 2004)
This paper analyses the dynamics of food exchange among Cook Islanders. The majority of Cook Islanders live abroad (primarily in New Zealand and Australia), familial and community relationships are maintained by frequent visits to and from the Cook Islands. For many Cook Islanders, the difference between home and abroad is signified through food. Its lack in New Zealand is contrasted with the bounty of home, bounty of food, and the bounty of sustaining caring relationships. As a result, when Cook Islanders from home visit family abroad, they take large quantities of local food with them. This paper explores the affective materiality of food that travels between Cook Islands